Education marketing management from the total quality management (TQM) perspective: A case study of a Muhammadiyah Islamic primary school - Muttaqin, Ziyadul (Tadibia Islamika: Journal of Holistic Islamic Education, 2024)
Educational marketing management is crucial for the sustainability of an educational institution. To attract more clients for educational services, institutions require effective marketing strategies. The role of the Principal as a manager in implementing these strategies is vital. This research analyzes the Principal's role in educational marketing management at SD Muhammadiyah Limpung from a Total Quality Management (TQM) perspective. The research addresses three key questions: (1) What is the strategic role of the Principal in marketing SD Muhammadiyah Limpung from a TQM perspective? (2) What strategies are employed in the educational marketing management at SD Muhammadiyah Limpung? (3) What are the impacts of implementing educational marketing? Using a qualitative research method and a case study design, data were collected through interviews, observations, and document analysis, including journals and other sources. The findings reveal that the Principal plays a crucial role in school management. The educational marketing strategy at SD Muhammadiyah Limpung, viewed through the TQM lens, is implemented using the 7Ps framework: product, price, place, promotion, people, physical evidence, and process. The impacts of implementing these educational marketing strategies include: 1) improved educational quality, 2) increased parental involvement, 3) enhanced school reputation and image, 4) increased student satisfaction, and 5) continuous innovation and improvement.